2020
DOI: 10.1111/1753-0407.13046
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and 6‐month dose of basal insulin associated with HbA1c achievement <7.0% in Chinese people with type 2 diabetes: results from the Observational Registry of Basal Insulin Treatment (ORBIT)

Abstract: Background:The efficacy of basal insulin (BI) for adequate glycemic control in patients with type 2 diabetes mellitus (T2DM) has been well documented by randomized clinical trials. This post-hoc analysis of the ORBIT study was performed to explore the 6-month dose of BI used 3 / 18 in insulin-naïve T2DM patients achieving HbA1c target (<7%) and determine the patient characteristics that affect the 6-month dose of BI in the setting of real-world clinics in China.Methods: This multicenter observational registry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Moreover, we investigated the factors that might influence the choice of insulin regimens of the doctors, and we found that the doctors preferred to prescribe twice‐daily premixed insulin (31.98 [11.04] IU/d at initiation) rather than once‐daily basal insulin (12.51 [5.38] IU/d at initiation) to those who had higher BMI and HbA1c levels at initiation. The daily insulin dosages used in the present study in each group were similar to those found in other studies 15,23 . These findings suggested that doctors preferred the twice‐daily administration of insulin to those with higher insulin dosages used (given on the basis of patient body weight) or with poorer glycemic control at initiation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, we investigated the factors that might influence the choice of insulin regimens of the doctors, and we found that the doctors preferred to prescribe twice‐daily premixed insulin (31.98 [11.04] IU/d at initiation) rather than once‐daily basal insulin (12.51 [5.38] IU/d at initiation) to those who had higher BMI and HbA1c levels at initiation. The daily insulin dosages used in the present study in each group were similar to those found in other studies 15,23 . These findings suggested that doctors preferred the twice‐daily administration of insulin to those with higher insulin dosages used (given on the basis of patient body weight) or with poorer glycemic control at initiation.…”
Section: Discussionsupporting
confidence: 85%
“…The daily insulin dosages used in the present study in each group were similar to those found in other studies. 15 , 23 These findings suggested that doctors preferred the twice‐daily administration of insulin to those with higher insulin dosages used (given on the basis of patient body weight) or with poorer glycemic control at initiation. However, when we further stratified patients into different HbA1c and BMI subgroups, the results showed no difference in the efficacies of glycemic control between the two insulin treatment groups in either the HbA1c < 9% or ≥ 9% subgroups ( p = 0.64 and 0.21, respectively) or the BMI < 25 or ≥ 25 kg/m 2 subgroups ( p = 0.95, and 0.23, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the study, the mean (±SD) dose of glargine was 0.22 ± 0.08 and 0.15 ± 0.06 units/kg/day for NPH. 16…”
Section: Glargine Versus Nphmentioning
confidence: 99%
“…Diabetes and related comorbidities were the leading cause of death in China in 2019 [ 2 ]. Chinese T2DM patients are characterized by a relatively young age, a low BMI, and significant IR [ 3 , 4 ]. It is well documented that the two major pathological features of T2DM are IR and β-cell dysfunction [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%